Inter- and intra-microcycle external load analysis in female professional soccer players: a playing position approach - Diaz-Seradilla, E.; Rodríguez-Fernández, A.; Rodríguez-Marroyo, J. A.; Castillo, D.; Raya-González, J.; Vicente, J. G. V. (PLOS ONE, 2022)
This study analyzes the inter- and intra-differences in external load across the microcycle in professional female soccer players. External load during four consecutive microcycles (i.e., M1, M2, M3, and M4) and training sessions (i.e., MD-4, MD-3, MD-2, and MD-1) and a match day (i.e., MD) were registered in seventeen female professional soccer players (age: 26.3 ± 4.6 years; height: 166.3 ± 6.1 cm; body mass: 59.8 ± 6.8 kg; and body mass index: 21.6 ± 1.7 kg·m-2) who belonged to the same team in Spanish first division. A 10-Hz GPS that integrated a 100-Hz triaxial accelerometer was used to register external load. The results showed lower decelerations in M2 compared to M1 and M3 (p < 0.05), lower high-intensity distance (>16.0 km·h-1) in M3 vs. M2, and greater relative sprint distance (>21.0 km·min-1) in M4 vs. M1 and M3 (p < 0.05). MD-3 registered the highest load for all variables (p < 0.05). Forwards (FWs) performed (p < 0.05) significantly more sprints (meters and number > 21.0 km·h-1) than central midfielders (CMs) and central defenders (CDs) in MD-2 and MD. Both, fitness and conditioning staff should pay special attention to the external loads for each playing position in training sessions to optimize the training process.